2000
DOI: 10.1023/a:1010386102562
|View full text |Cite
|
Sign up to set email alerts
|

Combined Vitamins B12b and C Induce the Glutathione Depletion and the Death of Epidermoid Human Larynx Carcinoma Cells HEp-2

Abstract: The combination of hydroxocobalamin (vitamin B12b) and ascorbic acid (vitamin C) can cause the death of tumor cells at the concentrations of the components at which they are nontoxic when administered separately. This cytotoxic action on epidermoid human larynx carcinoma cells HEp-2 in vitro is shown to be due to the hydrogen peroxide generated by the combination of vitamins B12b and C. The drop in the glutathione level preceding cell death was found to be the result of combined action of the vitamins. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It has been shown earlier that cobalamins are capable of catalyzing the formation of reactive oxygen species in the presence of natural reducing agents, e.g., ascorbate and thiols, which leads to oxidative stress [13][14][15]. We have found that hydroxycobalamin (B 12b ) in combination with ascorbate and thiol antioxidants GSH, NAC, and DTT catalyzes the formation and accumulation of hydrogen peroxide in medium, inducing single-and double-strand DNA breaks and the damage to lysosomes, which ultimately led to apoptoptic cell death [16][17][18][19]. Recently, we have shown that B 12b catalyzes the oxidation of diethyldithiocarbamate (DDC), a member of another group of thiol-containing substances, namely dithiocarbamates (DTC) [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown earlier that cobalamins are capable of catalyzing the formation of reactive oxygen species in the presence of natural reducing agents, e.g., ascorbate and thiols, which leads to oxidative stress [13][14][15]. We have found that hydroxycobalamin (B 12b ) in combination with ascorbate and thiol antioxidants GSH, NAC, and DTT catalyzes the formation and accumulation of hydrogen peroxide in medium, inducing single-and double-strand DNA breaks and the damage to lysosomes, which ultimately led to apoptoptic cell death [16][17][18][19]. Recently, we have shown that B 12b catalyzes the oxidation of diethyldithiocarbamate (DDC), a member of another group of thiol-containing substances, namely dithiocarbamates (DTC) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Modification of one of the constituents (i.e. brominated VK 3 ) or replacement of the VK 3 with any number of constituents (arsenic trioxide, benzoquinones, coenzyme Q10, doxorubicin, lipoic acid, resveratrol, vitamin B12, Vitamin E and others) [67,[80][81][82][83][84][85].…”
Section: Discussionmentioning
confidence: 99%
“…It is established that antioxidants combined with metals of variable valence may form prooxidant catalytic systems. An example of such a system is ascorbate combined with organic complexes of copper or cobalt, such as vitamin B 12b or cobalt phthalocyanines, which were used as antitumor agents during the past years [2][3][4][5][6][7]. However, it is unclear how thiols may serve as prooxidants in combination with vitamin B 12b .…”
mentioning
confidence: 99%
“…The agents studied were added 24 h after the plating 350 000 HEp-2 cells in T25 flasks. The calibration was performed by addition of H 2 O 2 into the experimental chamber after catalase [7].…”
mentioning
confidence: 99%